1980
DOI: 10.2307/1239475
|View full text |Cite
|
Sign up to set email alerts
|

Price Endogenous Mathematical Programming As a Tool for Sector Analysis

Abstract: The question, "Why use a mathematical programming model at the sectoral level?" is addressed. To address this question, discussion is presented mathematically and verbally upon mathematical programming sector models in which both price and quantity are eŸ variables. The discussion covers both the theoretical properties and the empirical concerns which must be faced in applying such models. Discussion is also presented upon the usefulness of the modeling approach for policy analysis. Selected bibliograpic citat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(127 citation statements)
references
References 17 publications
0
124
0
3
Order By: Relevance
“…Demand for food and wood is determined by exogenous population and gross domestic product (GDP) per capita projections and by projections of dietary patterns and trends (53). Equilibrium prices are the result of a simulation to maximize the sum of the producer and consumer surpluses (54). The maximization problem is subject to resource, technological, and policy constraints (55).…”
Section: Methodsmentioning
confidence: 99%
“…Demand for food and wood is determined by exogenous population and gross domestic product (GDP) per capita projections and by projections of dietary patterns and trends (53). Equilibrium prices are the result of a simulation to maximize the sum of the producer and consumer surpluses (54). The maximization problem is subject to resource, technological, and policy constraints (55).…”
Section: Methodsmentioning
confidence: 99%
“…Sector models of agriculture simulating competitive markets under fixed resources and production technology have long been common tools in agricultural economics (McCarl and Spreen 1980). Farmland resources are typically assumed to be fixed, while quasi-fixed inputs, such as buildings and machinery, typically have a lifespan of 10-30 years.…”
Section: Resultsmentioning
confidence: 99%
“…McCarl and Spreen (1980) compare the linear programming models used by other planned economic systems to the price endogenous model, and the results showed that the price endogenous model can represent the economic system in a perfectly competitive market. The model is useful in the policy analysis including the soil conservation policy , the global climate change (Adams et al 1986;McCarl et al 1999;Reilly et al 2002), and the climate change mitigation (McCarl and Schneider 2000).…”
Section: Mathematical Programming Analysis: Modified Taiwan Agricultumentioning
confidence: 99%